Efeito da idade na composição química, parâmetros colorimétricos e resistência biológica da madeira de Tectona grandis L. f. - Silva, Gabriel Afonso de Oliveira (2022)
The rapid growth of teak (Tectona grandis Linn. F) in some regions of Brazil stimulated large-scale planting for the production of sawn wood for the foreign market. However, within the production process there is material with little known properties, such as material from thinning. In this sense, characterization studies of teak wood at different ages are necessary to generate information related to the quality of these materials. Thus, the objective of this research was to evaluate the effect of age on the chemical composition, colorimetric parameters and natural strength of the wood of Tectona grandis L. f. The discs of the base of teak trees with 5, 10, 15 and 20 years from a commercial plantation located in the municipality of Nova Maringá, Mato Grosso, Brazil, were evaluated. Heartwood percentage, elemental and structural chemical composition were evaluated with qualitative analyzes by gas chromatography coupled to mass spectrometry (GC-MS), colorimetric parameters of the CIELab system and natural resistance to Trametes versicolor, a white rot fungus. The percentage of heartwood ranged from 21.35 to 62.58, for 5 and 20 years, respectively. In the elemental composition, there was an increase in carbon contents, from 51.13% to 53.86%, and a decrease in nitrogen and oxygen, from 0.11% to 0.05% and 44.04% to 41.25%, respectively. , with increasing age. There was no trend in the variation of the chemical structural constituents of teak wood. At the ages of 5 and 20 years, the percentage of total extractives was similar, 7.39 and 7.65%, respectively. However, the presence of tectoquinone and lapachol were higher for 20-year-old wood (45.03% and 10.23%) than for 5-year-old wood (39.97% and 4.31%). The woods with the highest proportion of heartwood showed greater red pigmentation and the yellow pigmentation progressively decreased with the age of the trees. Regarding saturation, the woods are considered opaque and there is a predominance of the yellow tone of the teak wood color. The removal of extractives from the wood influenced the increase in luminosity of 10, 15 and 20 year old woods. For the natural resistance to decay by white rot fungus, the 5-year-old wood was considered resistant and the 20-year-old wood very resistant after 12 and 16 weeks of testing. It is concluded that the properties of teak wood vary significantly with age and woods from fast-growing plantations have chemical characteristics and natural durability that are attractive to the consumer market.